1) 4c-(c-2)-(c-4)^2 2) (a-4)^2-2a(3a-4) 3) (a-3)(a-7)-2a(3a-5) 4) (a-c)(a+c)-(3a-c) 5) (c+2)(c-3)-(c-1)^2

1) 4c-(c-2)-(c-4)^2
2) (a-4)^2-2a(3a-4)
3) (a-3)(a-7)-2a(3a-5)
4) (a-c)(a+c)-(3a-c)
5) (c+2)(c-3)-(c-1)^2

  • 1) 4c-c+2-c^2+8c-16=-с^2+11c-14

    2) a^2-8a+16-6a^2+8a=-5a^2+16

    3) a^2-7a-3a+21-6a^2+10a=-5a^2+21

    4) a^2+ac-ac-c^2-3a+c=a^2-c^2-3a+c=a(a-3)-c(c-1)

    5) c^2-3c+2c-6-c^2+2c-1=c-7

  • 1)...=4c-c+2-(c^2-8c+16)=3c+2-c^2+8c-16==-c^2+11c-16

    2)...=a^2-8a+16-6a^2+8a=16-5a^2

    3)...=a^2-7a-3a+21-6a^2+10a=-5a^2+21

    4)...=a^2-c^2-3a+c

    5)...=c^2-3c+2c-6-(c^2-2c+1)=c^2-c-6-c^2+2c-1==c-7